2017
DOI: 10.1186/s10194-016-0714-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between right-to-left shunt and brain white matter lesions in Japanese patients with migraine: a single center study

Abstract: BackgroundThere may be a link between right-to-left shunt (RLs) and brain white matter lesions (WMLs) in patients with migraine. In this study, we assessed the relationship between WMLs and RLs in Japanese migraine patients.MethodsA total of 107 consecutive patients with migraine with (MA) and without aura (MWOA) were included in this study. Contrast transcranial Doppler ultrasound was used to detect RLs. WMLs were graded using brain magnetic resonance imaging based on well-established criteria.FindingsThe pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…Disease duration and attack frequency, as reported in the literature (9,24), were found to have no association with DWMHs in our study. Contrary to what we expected, we found a negative association with family history.…”
Section: Migraine Featuressupporting
confidence: 57%
See 1 more Smart Citation
“…Disease duration and attack frequency, as reported in the literature (9,24), were found to have no association with DWMHs in our study. Contrary to what we expected, we found a negative association with family history.…”
Section: Migraine Featuressupporting
confidence: 57%
“…The association between RLS and WMHs in migraine patients has long been debated. The majority of published papers have reported no association between RLS and WMHs (7,9,23); however, some research has shown a positive association (24,25). There is evidence that migraine patients have a higher prevalence of RLS (9, 10), and it is believed that paradoxical embolism caused by RLS is related to cryptogenic stroke and silent brain infarcts in migraine (26).…”
Section: Rls and Dwmhs In Migrainementioning
confidence: 99%
“…Our findings based on retrospective observation suggest a significant relationship between PFO and near- reported that right to left shunt is an independent risk factor for WMLs in migraine patients 16 , though further analysis of the WMLs was not carried out.…”
Section: Discussionmentioning
confidence: 67%
“…Emboli block microcirculation and cause local blood flow hypoperfusion 15 . In 2017, Farzianpour's study of 107 Japanese migraine patients reported that right to left shunt is an independent risk factor for WMLs in migraine patients 16 , though further analysis of the WMLs was not carried out.…”
Section: Discussionmentioning
confidence: 99%
“…while several studies did not show an association between the presence of RLS and WMH [52][53][54][55], some studies reported an association between RLS and certain types of WMHs in migraineurs [56][57][58].…”
Section: Factors Associated With Wmh In Migraineursmentioning
confidence: 93%